2020
DOI: 10.1007/s13592-020-00737-6
|View full text |Cite
|
Sign up to set email alerts
|

The miticide thymol in combination with trace levels of the neonicotinoid imidacloprid reduces visual learning performance in honey bees (Apis mellifera)

Abstract: Despite growing concerns over the impacts of agricultural pesticides on honey bee health, miticides (a group of pesticides used within hives to kill bee parasites) have received little attention. We know very little about how miticides might affect bee cognition, particularly in interaction with other known stressors, such as crop insecticides. Visual learning is essential for foraging bees to find their way to flowers, recognize them, and fly back to the nest. Using a standardized aversive visual conditioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 52 publications
1
11
0
2
Order By: Relevance
“…Numerous studies have shown that imidacloprid (e.g., [ 112 , 113 , 114 , 115 , 116 ]) and glyphosate [ 117 , 118 , 119 , 120 , 121 , 122 ] induce adverse sublethal effects in honey bees at the behavioral and physiological levels. It is noteworthy that imidacloprid elicits sublethal effects at exposure levels for which no interaction with its primary target (the nicotinic acetylcholine receptors [ 123 ]), responsible for the lethal insecticide effect, could be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that imidacloprid (e.g., [ 112 , 113 , 114 , 115 , 116 ]) and glyphosate [ 117 , 118 , 119 , 120 , 121 , 122 ] induce adverse sublethal effects in honey bees at the behavioral and physiological levels. It is noteworthy that imidacloprid elicits sublethal effects at exposure levels for which no interaction with its primary target (the nicotinic acetylcholine receptors [ 123 ]), responsible for the lethal insecticide effect, could be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Thymol is one of the phytochemicals most well studied for promoting bee health (Costa et al., 2010) and is used as a miticide treatment inside honey bee colonies (Gregorc & Planinc, 2013; Imdorf et al., 1995). However, the treatments come at a cost: A recent study revealed Apis mellifera simultaneously treated with thymol and IMD performed worse on visual learning tests than bees exposed to either chemical alone (Colin et al., 2020). Thus, beyond the shortened life spans reported here, doubly exposed bees run the risk of less efficient pollination (Gegear et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In Australia honey bees exposed to 5 ppb imidacloprid were found to forage at a younger age but to accumulate less food on the long term 17,18 . Additional effects that have been reported include: increased water consumption 11 , decreased foraging performance 19 , higher bee cluster temperatures 20 and reduced learning performance when mixed with another pesticide 21 . Even so, other studies have reported no individual effects at these low levels 19,22,23 .…”
Section: Introductionmentioning
confidence: 96%